ANALISIS PENGARUH INJEKSI GAS TETRAFLOROETANA TERHADAP KEKUATAN DIELEKTRIK GAS KARBONDIOKSIDA DALAM MEDAN TINGGI AC NON-HOMOGEN - A. Ihsanul Amal; Moch. Dhofir; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2022)
This study describes the effect of Tetrafluoroethane concentration on the dielectric of Carbondioxide gas in a non-homogen AC high field. This research begins with data collection through breakdown voltage testing at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Universitas Brawijaya. Variations of conditions used in the breakdown voltage test include changes in the concentration of Tetrafluoroethane into Carbondioxide gas of 0%, 10%, 20%, and 30% which are calculated based on the total pressure of the mixed gas, the variation of the total pressure of the mixed gas is 2000 mBar, 2200 mBar, 2400 mBar, and 2600 mBar, as well as changes in the gap between 1.5 cm and 3 cm. The test is carried out using high voltage AC. The arrangement of the electrodes used is a needle - plate. The results obtained in this study are the influence of the concentration of R134 into CO₂ gas where the value of the dielectric strength of pure CO₂ gas is lower than that of contaminated CO₂ gas, in this case R134 is the impurity. In addition, variations in the concentration ratio of R134 from 0% to 30% and variations in the ratio of total mixed gas pressure from 2000 mBar to 2600 mBar affect the dielectric strength of the mixed gas. Where the greater the concentration value of R134, the greater the breakdown voltage value and the greater the total pressure value of the mixed gas, the greater the breakdown voltage value. Index terms—Gas Insulator, Carbondioxide, Tetrafluorethane, Breakdown Voltage, Dielectric Streng